A new species of the Boulenophrys (Anura, Megophryidae) from Hubei, China - Shize Li; Shengchao Shi; Jing Liu; Jingjing Zhao; Shuo Gao; Bin Wang (Zoosystematics and Evolution, 2025)
A new species of Asian horned toad, Boulenophrys, is described from Changyang County, Hubei Province, China. The new species differs from its congeners by the following combination of characters: (1) body size moderate (SVL 39.4–43.3 mm in males); (2) a small horn-like tubercle at the edge of each upper eyelid; (3) vomerine ridges weak and vomerine teeth absent; (4) tongue not notched posteriorly; (5) head width greater than head length; (6) no large, pale-white circular spots on the shoulders; (7) toes without webbing or lateral fringes; (8) heels overlapping when thighs are positioned at right angles to the body; (9) tibiotarsal articulation reaching the level of the middle of the eye when the leg is stretched forward; (10) an internal single subgular vocal sac in males; and (11) in breeding males, nuptial pads bearing black nuptial spines on the dorsal bases of the first and second fingers.